2016
DOI: 10.1159/000441951
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Delivered Disease Management for Recurrent Depression: A Multicenter Randomized Controlled Trial

Abstract: Background: Strategies to improve the life of patients suffering from recurrent major depression have a high relevance. This study examined the efficacy of 2 Internet-delivered augmentation strategies that aim to prolong symptom-free intervals. Methods: Efficacy was tested in a 3-arm, multicenter, open-label, evaluator-blind, randomized controlled trial. Upon discharge from inpatient mental health care, 232 adults with 3 or more major depressive episodes were randomized to 1 of 2 intervention groups (SUMMIT or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 39 publications
(70 reference statements)
1
46
0
3
Order By: Relevance
“…Additionally, this meta-analysis found that larger effects were only observed for MoodGYM in studies that involved face-to-face guidance, whereas effects were small (g = 0.23, NNT = 7.7) when remote guidance by telephone or email was provided, and there was no evidence to suggest that the programme was effective without any guidance. However, guidance does not always enhance the effects of Internet interventions, as several trials have not found larger effects when guidance was provided, and a meta-analysis suggested that the effects of guidance may be less pronounced than often assumed [34][35][36]. In our meta-analysis, the effect sizes for deprexis were in the clinically relevant range regardless of whether no guidance or some guidance was provided.…”
Section: Comparisons With Other Studiesmentioning
confidence: 52%
“…Additionally, this meta-analysis found that larger effects were only observed for MoodGYM in studies that involved face-to-face guidance, whereas effects were small (g = 0.23, NNT = 7.7) when remote guidance by telephone or email was provided, and there was no evidence to suggest that the programme was effective without any guidance. However, guidance does not always enhance the effects of Internet interventions, as several trials have not found larger effects when guidance was provided, and a meta-analysis suggested that the effects of guidance may be less pronounced than often assumed [34][35][36]. In our meta-analysis, the effect sizes for deprexis were in the clinically relevant range regardless of whether no guidance or some guidance was provided.…”
Section: Comparisons With Other Studiesmentioning
confidence: 52%
“…These comprise integrative care approaches organized in disease management programs and long-term support with low-threshold therapeutic contacts. For example, a fully automated internet-delivered augmentation strategy (SUMMIT) was superior to treatment as usual in patients with recurrent depression over 24 months after discharge [45]. …”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of Internet interventions in routine clinical settings has recently been questioned as one study failed to demonstrate the superiority of two Internet interventions with telephone guidance over usual care in participants with at least moderate depressive symptoms recruited through their general practitioners [14]. Another recent study has demonstrated the efficacy of an Internet intervention following inpatient treatment [15]. …”
Section: Introductionmentioning
confidence: 99%